Snow white and the seven dwarfs - Rollason, Jane; Rollason, Jane (London York press, 2020)
Snow white's new mother, the queen, isn't nice or kind and she takes snow white to the forest, in the forest, snow white finds a small house. in the house, she finds seven dwarfs with seven deds, the dwarfs are kind to snow white and she is happy
English stories
1
Keywords: English stories